The Connection Between Rap1 and Talin1 in the Activation of Integrins in Blood Cells - Sun, Hao; Lagarrigue, Frederic; Ginsberg, Mark H. (Frontiers in Cell and Developmental Biology, 2022)
Integrins regulate the adhesion and migration of blood cells to ensure the proper positioning of these cells in the environment. Integrins detect physical and chemical stimuli in the extracellular matrix and regulate signaling pathways in blood cells that mediate their functions. Integrins are usually in a resting state in blood cells until agonist stimulation results in a high-affinity conformation (“integrin activation”), which is central to integrins’ contribution to blood cells’ trafficking and functions. In this review, we summarize the mechanisms of integrin activation in blood cells with a focus on recent advances understanding of mechanisms whereby Rap1 regulates talin1-integrin interaction to trigger integrin activation in lymphocytes, platelets, and neutrophils.